Autoantibodies of IgM and IgG classes show differences in recognition of multiple autoantigens in chronic obstructive pulmonary disease - Shindi, Reham; Al-Mehairi, Amna; Negm, Ola H.; Kalsheker, Noor; Gale, Nichola; Shale, Dennis J.; Harrison, Timothy W.; Bolton, Charlotte E.; John, Michelle; Todd, Ian; Tighe, Patrick J.; Fairclough, Lucy C. (Elsevier, 2017)
Autoimmunity occurs in chronic obstructive pulmonary disease (COPD). We describe an antigen microarray for detecting serum autoantibodies (AAbs) to determine how IgM, as well as IgG, AAbs distinguish patients with COPD from controls with a history of smoking without COPD. All COPD patients' sera contained elevated levels of AAbs to some of 30 autoantigens. There were significant differences in the autoantigenic specificities of IgM AAbs compared to IgG AAbs in the COPD sera: for example, AAbs to histone and scl-70 were mainly IgG, whereas AAbs to CENP-B and La/ssB were mainly IgM; by contrast, IgM and IgG AAbs to collagen-V were equally prevalent. Thus, a combination of IgM and IgG AAbs specific for multiple autoantigens are detected in all cases of COPD at a level at which all non-COPD controls are negative for AAbs. This highlights the importance of different classes of AAbs to a range of autoantigens in COPD.